Estudo e aplicação da manutenção centrada na confiabilidade na central de água gelada de uma aciaria - Morais, Giussepp Kelson Castro (2017)
This work intends to apply the Reliability Centered Maintenance methodology based on the FMECA tool (Criticality Analysis, Modes and Effects of Failures in the Cold Water Center (CAG), which is responsible for air conditioning in the electric and control rooms of the Steelworks. The initial phase of this work consists in the elaboration of a descriptive of the operational context, containing the information necessary for a complete understanding of the process where CAG is applied, the role and its relevance to the company's business. operation and maintenance will be related to the CAG functions along with the performance standards and their functional failures. Failure modes of functional failures will be defined through the failure histories recorded in the SISMANA (ArcelorMittal Tubarão Maintenance Management System), experience inspectors and equipment manual. o the degree of risk of each mode of failure based on its severity, occurrence and detectability to later be classified in order of priority. The fault modes classified with high and medium criticality will be directed to a decision matrix where they will define the best maintenance strategy for the items. Fault modes classified with low criticality will be treated with corrective tasks. Once the tasks that meet the requirements for technical feasibility and cost effectiveness for the management of each failure mode are defined, they will be entered into the Sismana through inspection plans or services. After completion of the FMECA a list of critical spare parts will be created based on the economic viability of performing a task by condition / restoration or corrective task if the lack of the spare interferes with the main function of the CAG, cost and lead time of the spare. Due to the existence of only one Chiller (equipment intended to cool the water) in the CAG, a contingency plan will be prepared to mitigate the risks in case of functional failure of the CAG. During the study, difficulties will be encountered, such as lack of data, information and routine tasks competing with the preparation of this work, but alternatives should be sought so as not to compromise the results. We hope to apply this study to optimize maintenance plans, reducing costs with corrective and preventive maintenance, increasing plant reliability.